2004
DOI: 10.1002/anie.200453937
|View full text |Cite
|
Sign up to set email alerts
|

Sceptrin as a Potential Biosynthetic Precursor to Complex Pyrrole–Imidazole Alkaloids: The Total Synthesis of Ageliferin

Abstract: Microwave‐induced magic: There is a widely held conviction that the antiviral marine alkaloid ageliferin 1 arises biosynthetically from a Diels–Alder reaction which, although possible, has yet to materialize in the laboratory. A total synthesis of 1 from sceptrin is now reported that has led to a new hypothesis for how 1 and other dimeric pyrrole‐imidazole alkaloids might be formed in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 20 publications
5
96
0
Order By: Relevance
“…[3][4][5][6] The calculated pK a of 1-H + of +10.9 in aqueous solution indeed suggests that 1 is present quantitatively in its protonated form even under mildly acidic reaction conditions. Protonation also decreases the stability difference between the most stable tautomer III and the less stable tautomer IV, offering an explanation for the apparent involvement of this latter tautomer in H/D exchange experiments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[3][4][5][6] The calculated pK a of 1-H + of +10.9 in aqueous solution indeed suggests that 1 is present quantitatively in its protonated form even under mildly acidic reaction conditions. Protonation also decreases the stability difference between the most stable tautomer III and the less stable tautomer IV, offering an explanation for the apparent involvement of this latter tautomer in H/D exchange experiments.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4][5][6] The flexible use of this building block in the biosynthesis of pyrrole-imidazole alkaloids has recently been suggested to be due to the variable reactivity of 1, acting as a nucleophile in tautomeric forms I and III and as electrophile in tautomeric forms II and IV. Equilibration between the respective tautomeric forms thus stands at the center of a comprehensive biosynthetic scheme proposed by Al-Mourabit et al [1] In order to support the participation of different tautomeric forms of 1 along various biosynthetic pathways, Al-Mourabit et al have recently described the results of theoretical studies suggesting the comparable stability of the four tautomeric forms I-IV of 1 shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Baran et al, where the authors converted the natural product Sceptrin into Ageliferin under microwave-assisted conditions [116]. While attempting to rationalize the presence of Sceptrin as the major product during the biosynthesis of Ageliferin, the authors managed an ingenious interconversion of Sceptrin to Ageliferin simply by shifting the thermodynamic equilibrium of the reaction (Scheme 31).…”
Section: B Das Et Al Have Demonstrated a Microwave-assisted Modificmentioning
confidence: 98%
“…Multidentate N-heterocycles on coordination to metal ions produce organized supramolecules and they appear quite promising for the design of stable light conversion devices [11]. The application of imidazoles in medicinal chemistry [12] and chemistry of natural products/alkaloids [13,14] are also well known. Heterocycles containing the imidazole moiety are of biological significance and display antibacterial, antifungal activities [15], leukotriene B 4 receptor antagonist properties [16], and potassium channel openers [17].…”
Section: Introductionmentioning
confidence: 99%